Repairing Rationality: Max Bense and the Automation of Literature in Post-War Germany. - Holt, Matthew (Australian Literary Studies)
The article focuses on the work of German philosopher, information theorist, and poet Max Bense and his postwar theories of machine intelligence and literary automation in Germany. It examines how Bense connected artificial intelligence, aesthetics, and literary experimentation as a reparative response to the legacy of fascism, using information aesthetics to rethink rationality, creativity, and the relationship between human and machine language.